2018
DOI: 10.1002/eji.201747150
|View full text |Cite
|
Sign up to set email alerts
|

The vaccine adjuvant alum promotes IL‐10 production that suppresses Th1 responses

Abstract: The effectiveness of many vaccines licensed for clinical use relates to the induction of neutralising antibodies, facilitated by the inclusion of vaccine adjuvants, particularly alum. However, the ability of alum to preferentially promote humoral rather than cellular, particularly Th1-type responses, is not well understood. We demonstrate that alum activates immunosuppressive mechanisms following vaccination, which limit its capacity to induce Th1 responses. One of the key cytokines limiting excessive immune r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 48 publications
2
50
0
1
Order By: Relevance
“…Additionally, it has been demonstrated recently that alum adjuvant activates immunosuppressive mechanisms following vaccination with the help of increased production of IL-10 cytokine by macrophages and DCs, which limits its ability to induce Th1-type immune responses. 31 As observed in this study, the level of IL-10 cytokine in both AH nps immunized mice groups was statistically low as compared to the commercial adjuvant AH gel group (P< 0.001). Taken together with the results of enhanced productions of Th1-type cytokines, the decreased production of IL-10 cytokine indicates that the induction of Th1-type immune response in the crystalline and amorphous AH nps mice groups were not restrained.…”
Section: Figuresupporting
confidence: 64%
“…Additionally, it has been demonstrated recently that alum adjuvant activates immunosuppressive mechanisms following vaccination with the help of increased production of IL-10 cytokine by macrophages and DCs, which limits its ability to induce Th1-type immune responses. 31 As observed in this study, the level of IL-10 cytokine in both AH nps immunized mice groups was statistically low as compared to the commercial adjuvant AH gel group (P< 0.001). Taken together with the results of enhanced productions of Th1-type cytokines, the decreased production of IL-10 cytokine indicates that the induction of Th1-type immune response in the crystalline and amorphous AH nps mice groups were not restrained.…”
Section: Figuresupporting
confidence: 64%
“…Alum can induce modest Ag-specific CD8 + responses in mice following vaccination by i.p. (17) or i.m. routes (18).…”
mentioning
confidence: 99%
“…Alumina NPs have a self-adjuvant effect, and some studies have focused on their mechanism of action, for example, activation of the NACHT, LRR and PYD domains-containing protein 3 (NALP3) inflammasome in DCs (Eisenbarth, Colegio, O'Connor, Sutterwala, & Flavell, 2008;Kool et al, 2008). Ewa Oleszycka et al found that alum-mediated adjuvant works by suppressing Th1 responses and the key cytokines IL-10 which suppressed Th1 responses promoted by priming DLN cells after injection of alum (Oleszycka et al, 2018). Haiyan et al reported a nanovaccine composed of α-Al 2 O 3 as antigens carrier.…”
Section: Metal-based Nanovaccinementioning
confidence: 99%